(untitled) (INNOVATIVE ECONOMY, 2020)
Yakovets T.A., Kovalchuk Y.P. NEW KINDS OF MONEY: REALITIES OF THEIR USE, ACCOUNTING AND PECULIARITIES OF TAXATION Purpose. The purpose of this article is the investigation of problems of use, accounting, taxation of electronic money and cybercurrency to find ways to overcome them and ensure the effective functioning of domestic economic system. Methodology of research. The research process was conducted using a dialectical approach to the study of the current state of accounting and reporting of new forms of money and cryptocurrency and using methods of cognition, deduction and abstract and logical cognition to determine the essence of electronic money; abstraction and concretization to improve the interpretation of the essence of new money; grouping, comparison, generalization in the study of domestic and international legislative principles on the regulation of the circulation of cryptocurrency; modeling to develop proposals for improving the accounting of electronic money and cryptocurrency using the plan of accounts. Findings. The basic tendencies of introduction of the newest forms of means of payment and calculation of electronic money and cryptocurrency are determined. It was established that the process of their functioning within the framework of the national economic system is slowing down due to the lack of legislative regulation of their use. The ways of improvement of the Tax Code in the part of taxation of transactions with electronic money are grounded. The comparison of national and international possibilities of using cryptocurrency in the course of financial and economic activity is carried out. Originality. The methodical approaches of cryptocurrency accounting are formulated by national business entities in the context of its purchase, mining and settlement of transactions. Practical value. The results of the investigation will contribute to the improvement of the legal justification of the essence and use of electronic money, reflection of transactions with them on the accounts of accounting. It can also serve as a basis for building a system of accounting and taxation of cryptocurrency. Key words: electronic money cryptocurrency; mining; intangible asset.